Continuous Improvement of IT Acquisition Process in Federal Public Organizations: Challenges in the Brazilian Context - Santos, Melquizedequi Cabral dos; Santos, Wylliams Barbosa; Oliveira, Sandro Ronaldo Bezerra; Vasconcelos, Alexandre Marcos Lins de; Silva, Carla (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Information systems (IS) are directly linked to the organizational processes of public or private organizations. In the context of Brazilian federal public organizations (OPFB), the information technology acquisition (ATI) process is one of the key to supporting IS in OPFB. The problem raised in this research is that existing ITA standards have limitations related to the procedures for continuous improvement. There are indications that there are challenges to be understood that may affect the quality of the ITA process, and consequently, of the IS generated from this process. The goal is to identify key challenges and thereby support IT managers when they are continually improving their ATI and IS related processes. For this, semi-structured interviews were conducted, analyzed through Grounded Theory techniques, together with managers and IT specialists from Brazilian federal public organizations. Some challenges emerged in the form of hypotheses such as: nature of hiring, process time, IT planning, communication, etc.